Orthodontic cements: immediate protection and fluoride release - Santos,Rogério Lacerda dos (2012)
OBJECTIVES: The objective of the authors was to evaluate fluoride release of 3 glass ionomer cements with immediate protection of fluoride varnish (Cavitine, SS White), divided into 3 groups: Group M (Meron, VOCO), Group V (Vidrion C, SS White) and Group KC (Ketac-Cem, 3M ESPE). METHODS: Fluoride release was measured during 60 days by means of an ion-selective electrode connected to an ion analyzer. After 4 weeks, the test specimens were exposed to a solution of 0.221% sodium fluoride (1000 ppm of fluoride). RESULTS: Results showed that the cements reached a maximum peak of fluoride release in a period of 24 h. There was a statistically significant difference between the amount of fluoride released after the applications of fluoride among the groups from the 31st to 60th day (p> 0.05). CONCLUSION: The Vidrion C and Meron cements showed better performance to uptake and release fluoride when compared with Ketac-Cem cement.